Nemški priseljenci v Mariboru - Godina-Golija, Maja (Etnolog. Nova vrsta (Ljubljana), 2016)
For centuries Maribor had a marked bilingual character. Population censuses as well as material remains manifest the significance of the German community in the town. Besides a few old German families of Maribor that had lived in the town for some generations, numerous German speaking immigrants moved to Maribor at the end of the 19th and at the beginning of the 20th century and shaped the image of the town with multiple cultural features. In the article, the author examines the material remains of their habitation by focusing on buildings and urban architecture, and on food and clothing culture.
Keywords: kulturna zgodovina; material culture; materialna kultura; the end of 19th and the beginning of 20th century; Maribor German population; nemški priseljenci; Nemci; heritage; Maribor; 19./20.st.